MANUSIA SEBAGAI MAKHLUK PEDAGOGIK: Pandangan Islam dan Barat - Slamet, Moh. Ibnu Sulaiman (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2017)
There are some schools in education such as; Pessi-mism, Optimism, Convergence, and Islam has view point that man has potential to be educated (Homo Educandum), the talent and environment constitute two convergence lines strive one focus, that is the man development, besides that as creature who can be educated, the man also needs education in order to develop himself. Because, as human being, man is substantially has capability to know the highest level, at once place them as social creature and cultural one that his growing and developing at culture totally, including education and also as human being, man has rational capability, from rational capability the man can study fro what is seen them. The man with this potential can develop himself as caliph who has some excellences from another creature.